TEKNOLOGI INFORMASI DAN KOMUNIKASI: KEDUDUKAN DAN PERANANNYA DALAM PENDIDIKAN - Umar Umar (Pascasarjana IAIN Metro, 2016)
Information and Communication Technology as a part of Science and Technology generally is the whole technology related to catching, collecting, storage processing, disseminating, and presenting of information. Information and Communication Technology Development has extraordinary impact in whole field of human life, include education field. The crucial problems strart from education policy which is reflected in changing curriculum, until the implementation in learning process. The others problem is the limited time allocation for presenting curriculum. Information and Communication Technology which has flexible role provide alternative solution in solving that problems.